The clan of the cave bear : a novel - Auel, Jean M. (Auel, Jean M. Earth's children., 1980)
The Clan of the cave bear is the first of Jean Auel's sensational Earth's Children series. Ayla, a tall, blond, blue-eyed girl lost her family in an earthquake. She is nurtured and protected by some members of the Clan, but there are those who would cast her out because of her strange and threatening ways. Ayla's adventures 25,000 years ago include exquisite details of our world as it might have been.